High-Frequency Oscillations on Interictal Epileptiform Discharges in Routinely Acquired Scalp EEG: Can It Be Used as a Prognostic Marker? - El Shakankiry, Hanan; Arnold, Susan T. (Frontiers in Human Neuroscience, 2021)
Despite all efforts for optimizing epilepsy management in children over the past decades, there is no clear consensus regarding whether to treat or not to treat epileptiform discharges after a first unprovoked seizure, or the optimal duration of therapy with anti-seizure medication (ASM). Defining what should be considered as a pathological EEG discharge that requires treatment on scalp EEG is therefore highly needed. Aim of the work: This retrospective study aimed to identify whether the coexistence of ripples/ high frequency oscillations (HFOs) with interictal epileptiform discharges in routinely acquired scalp EEG is associated with a higher risk of seizure recurrence and could be used as a prognostic marker. Methods: 100 children presenting with new onset seizures to Children Medical Center- Dallas during 2015-2016, who were not on ASM and had focal epileptiform discharges on an awake and sleep EEG recorded with sample frequency of 500 HZ, randomly were identified by database review. EEGs were analyzed blinded to patient’s data. HFOs were visually identified using review parameters including expanded time base and adjusted filter settings. Results: The average age of patients was 6.3 yrs (±4.35 SD). HFOs were visually identified in 19% of the studied patients with inter-rater reliability of 99% for HFO negative discharges and 78% agreement for identification of HFOs. HFOs were identified more often in the younger age group; however, they were identified in 11% of patients >5 yrs old. They were more frequently associated with spikes than with sharp waves, and more often with higher amplitude epileptiform discharges. Patients with HFOs were more likely to have recurrence of seizures in the year after first seizure (P< 0.05), and to continue to have seizures after two years (P<0.0001). There was no statistically significant difference between the two groups as regards continuing anti-seizure medications after 2 years. Conclusions: Including analysis for HFOs in routine EEG interpretation may increase the yield of the study and help guide the decision to start or discontinue ASM. In the future, this may also help identifying pathological discharges with deleterious effect on the growing brain and set a new target for management of epilepsy.